2011
DOI: 10.1523/jneurosci.1478-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prior Expectation Modulates the Interaction between Sensory and Prefrontal Regions in the Human Brain

Abstract: How do expectations about the identity of a forthcoming visual stimulus influence the neural mechanisms of perceptual decision making in the human brain? Previous investigations into this issue have mostly involved changing the subjects' attentional focus or the behavioral relevance of certain targets but rarely manipulated subjects' prior expectation about the likely identity of the stimulus. Also, because perceptual decisions were often paired with specific motor responses, it has been difficult to dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 45 publications
11
97
0
Order By: Relevance
“…On other hand, if the classifier performance is lower for both surprising and neutral events, then one can assume that there is an additional ɛ unit activity reduction, driven by correct predictions. Rahnev et al, (2011) also confirms this result when inducing expectations regarding the direction of a moving-dot pattern. Authors found a neural response enhancement for invalidly cued (therefore surprising) events when compared to expected and neutral events (with the expected cued activations falling in between the other two) in the dorsolateral prefrontal cortex and in the intraparietal sulcus.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On other hand, if the classifier performance is lower for both surprising and neutral events, then one can assume that there is an additional ɛ unit activity reduction, driven by correct predictions. Rahnev et al, (2011) also confirms this result when inducing expectations regarding the direction of a moving-dot pattern. Authors found a neural response enhancement for invalidly cued (therefore surprising) events when compared to expected and neutral events (with the expected cued activations falling in between the other two) in the dorsolateral prefrontal cortex and in the intraparietal sulcus.…”
Section: Discussionsupporting
confidence: 74%
“…These were corresponding to a previously suggested neutral or unpredicted condition (Rahnev et al, 2011;Kovács & Vogels, 2014) in which the probability of repeated (Rep) and alternated (Alt) trials was identical. The other four conditions were identical to those of Grotheer & Kovács (2015).…”
Section: Stimulation and Proceduresmentioning
confidence: 99%
“…Perceptions are greatly influenced by expectations [20]. Previous research has demonstrated how prior expectation might bias perceptual decisions [21,22]. We investigated whether an expectation of abnormality affects visual search by altering clinical information when looking for pulmonary nodules in adult chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…EEG recordings, however, do not offer comparable evidence concerning the underlying brain regions involved in specific computations. To better evaluate the reliability of the prediction/production parallel (Pickering & Garrod, 2007), it is important to identify the brain source of beta-band effects, that both production (Klein et al, 2014) and prediction studies (Rahnev et al, 2011) would identify in frontal brain regions.…”
Section: Oscillatory Dynamics Reflecting Pre-stimulus Predictionmentioning
confidence: 99%
“…Frontal regions would constitute a critical hub collecting abstract information preliminary to production/prediction. Previous studies (Bastos et al, 2015;Rahnev et al, 2011) in fact show that pre-frontal brain regions would drive the recruitment of source information to develop Forward Models and Sensory Predictions, i.e., pre-activation of lowlevel information (in peripheral sensory regions) related to the physical properties of the predicted stimulus. Enhanced expectations could thus modulate visual attention and the perception of an incoming stimulus (for a discussion of the relation between expectation and attention see Summerfield & Egner, 2009).…”
Section: To Be(ta) or Not To Be(ta): That Is The Questionmentioning
confidence: 99%